Technologies and innovation : third International Conference, CITI 2017, Guayaquil, Ecuador, October 24-27, 2017, Proceedings /: third International Conference, CITI 2017, Guayaquil, Ecuador, October 24-27, 2017, Proceedings. (2017) - Unknown
No abstract available